Six additional questions about smart specialization: implications for regional innovation policy 4.0 - Benner, Maximilian (European planning studies, 2020)
In response to the article ‘Six critical questions about smart specialization’ and Dominique Foray’s reply to that article, this paper identifies several more questions to be asked about the smart specialization approach and its implementation under EU cohesion policy in recent years. The paper argues that in addition to the critical points identified earlier, the smart specialization discourse has become overly focused on research and development, suffers from an unclear understanding of appropriate spatial scales, focuses too much on brands and policy documents and too little on process which leads to a number of crucial implementation challenges. The paper suggests refocusing the next, fourth generation of regional innovation strategies under EU cohesion policy towards a more heterogeneous paradigm that draws conclusions from the procedural progress made during the smart specialization era so far but allows for more situated experimentation within regions.